Initiation of RNA-primed DNA synthesis in vitro by DNA polymerase alpha-primase. - Harrington, C (1995)
The initiation of new DNA strands at origins of replication in animal cells requires de novo synthesis of RNA primers by primase and subsequent elongation from RNA primers by DNA polymerase alpha. To study the specificity of primer site selection by the DNA polymerase alpha-primase complex (pol alpha-primase), a natural DNA template containing a site for replication initiation was constructed. Two single-stranded DNA (ssDNA) molecules were hybridized to each other generating a duplex DNA molecule with an open helix replication 'bubble' to serve as an initiation zone. Pol alpha-primase recognizes the open helix region and initiates RNA-primed DNA synthesis at four specific sites that are rich in pyrimidine nucleotides. The priming site positioned nearest the ssDNA-dsDNA junction in the replication 'bubble' template is the preferred site for initiation. Using a 40 base oligonucleotide template containing the sequence of the preferred priming site, primase synthesizes RNA primers of 9 and 10 nt in length with the sequence 5'-(G)GAAGAAAGC-3'. These studies demonstrate that pol alpha-primase selects specific nucleotide sequences for RNA primer formation and suggest that the open helix structure of the replication 'bubble' directs pol alpha-primase to initiate RNA primer synthesis near the ssDNA-dsDNA junction.